Sacred marriage : what if God designed marriage to make us holy more than to make us happy? - Thomas, Gary (Zondervan, 2000)
"'Sacred Marriage' doesn't tell how to build a better marriage -- it shows how your marriage can help you deepen your relationship with God. From the practice of forgiveness, to the ecstasy of lovingmaking, to the history you and your spouse create together, everything about your marriage is filled with the potential for discovering and revealing Christ's character. Now with discussion questions for couples and small groups, this book may very well alter your marriage profoundly. It will most certainly change your. Because whether it is delightful or difficult, your marriage can become a doorway to a closer walk with God" --Cover, p. 4.